Contes licencieux de Polynésie à travers le prisme occidental : la fluidité des genres et le choc des cultures - Anthony Tchékémian; Philippe Prudhomme (Études Caribéennes)
Albert T’Sersteven’s article ‘Polynesia: a natural game’ explores Polynesian sexuality and social practices through a Western lens, published in 1934 in Le Mercure de France. The author examines the fluidity of sexual and gender roles in these societies, where the boundaries between the sexes are more flexible than in the Western world. He highlights the place of the mahou (effeminate men), respected figures who contrast with the rigid norms imposed by colonialism and Christianity. T’Sersteven observes that Polynesians had a spontaneous and free sexuality, albeit transformed by the arrival of Europeans. The author criticises the introduction of Christian morality and its notions of sin and repression, highlighting the cultural clash between local practices and Western values. Although sometimes exotic, the text questions the Western view of non-European cultures. Polynesian traditions, including homosexuality and the third gender, are respected, but colonial values seek to impose norms. The representation of the mahou as a sacred figure embodies the richness of a culture that defends its values against the imposition of European standards. Modern issues such as globalisation and climate change echo the contemporary challenges facing these societies.